Bridging Psychology and Law: The Role of Clinical Criminology in Criminal Behaviour Assessment and Rehabilitation - M, Ramesh; M, Mahalingam; Giftson D, Bennet Paul; Paul, Shubhankar; Sahoo, Girish Ranjan; Ji, Ganesh (Journal of Neonatal Surgery, 2025)
Intersecting the domains of psychology and law, clinical criminology is an important multidisciplinary discipline. This paper explores how clinical criminology aids in the assessment and rehabilitation of offenders by integrating psychological evaluation with criminological analysis. It severely discusses the usefulness of psychological tests in legal ruling such as criminal tolerance, competency and risks of recidence. It also examines the rehabilitative measures, such as cognitive-behavioural and trauma-informed treatments through the prism of empirical scholarly studies and according to the existing legal precedents, in the realm of correctional and forensic facilities. The paper takes the stand of moving towards therapeutic jurisprudence and more restorative conception of justice which take into account psychological aspects of criminal malpractices.